Enhancing Food Service Sales through AI and Automation in Convenience Store Kitchens - Sachani, Dipakkumar Kanubhai; Dhameliya, Niravkumar; Mullangi, Kishore; Anumandla, Sunil Kumar Reddy; Vennapusa, Sai Charan Reddy (Global Disclosure of Economics and Business, 2021)
According to one study, AI and automation may boost convenience store kitchen food service sales. The primary goals were to study how AI and automation technologies boost revenue, customer satisfaction, and operational efficiency. A review used secondary data from industry reports, case studies, and academic literature. Significant findings show that AI-driven predictive analytics improve inventory management by precisely estimating demand and decreasing waste and stockouts. Automatic cooking technology maintains food quality and speed, while self-service kiosks and mobile ordering platforms personalize client experiences and ease ordering, increasing sales and repeat business. Regulators must handle data privacy concerns and help workers adjust to new technologies. By meeting changing consumer expectations and operational constraints, convenience store kitchens can achieve sustainable growth and competitive advantage with strategic AI and automation.